PENGARUH LATIHAN HARNESS DAN LATIHAN PARACHUTE TERHADAP HASIL LARI 60 METER PADA MAHASISWA KOP ATLETIK UNJ - Marlita Hayun; Agus Kurniadi (Cahaya Ilmu Bangsa Institute, 2024)
The purpose of this study is to find out: 1) The effect of Harness training on the results of the 60-meter run in UNJ Athletic KOP students, 2) The effect of Parachute training on the results of the 60-meter run in UNJ Athletics KOP students, 3) Comparison of Harness training and Parachute training on the results of the 60-meter run in UNJ Athletics KOP students. The research method used is an experiment with the